Action of Carduus marianus 6cH on Hepatopathy and Gallstone in Ambystoma mexicanum (Axolotl): Case Report - Martins, Jéssica Amâncio; Balbueno, Melina Castilho de Souza; Coelho, Cidéli de Paula (Homeopathy, 2024)
Background Carduus marianus is a Mediterranean plant used for treating liver diseases. One of its properties is that it inhibits fat peroxidation, which can contribute toward the prevention of metabolites that are harmful to the liver.Objective The aim of this study was to describe the treatment of fatty liver disease in an axolotl (Ambystoma mexicanum).Methods An approximately 6-year-old female specimen of A. mexicanum, of length 21 cm and weight 153 g, presented edema in the rostral region and inappetence. Ultrasound showed hepatopathy and a gallbladder stone. A globule of C. marianus 6cH was diluted in 30 mL distilled water and administered in spray form over the animal twice a day.Results Twenty days after the beginning of the treatment, improvement of the facial edema and return of appetite were observed. Ultrasound showed improvement in the appearance of the liver and reduction in the size of the gallstone. The Modified Naranjo Criteria for Homeopathy score was +9 in this case, thus suggesting a causal relationship between the use of homeopathic medicine and the clinical outcome.Conclusion C. marianus 6cH appeared to be effective in treating fatty liver disease and gallstone in this specimen of A. mexicanum.
Keywords: axolotl; homeopathy; liver disease; milk thistle; salamander